Sir Cumference and the Great Knight of Angleland : A Math Adventure - Cindy Neuschwander (Watertown, United States Charlesbridge Publishing,U.S., 2001)
Radius is on a quest to earn his knighthood! With only a circular medallion, a mysterious poem, and his own wits to guide him, he must find and rescue a missing king.